Population Dynamics of Yellowstripe Scad (Selaroides leptolepis) in Lampung Bay Waters - Kartini, Nidya; Yudha, Indra Gumay; Yulianto, Herman; Caesario, Rachmad; Julian, David (Jurnal Biologi Tropis, 2024)
Yellowstripe scad (Selaroides leptolepis) is a type of pelagic fish that is dominantly caught in the waters of Lampung Bay and is landed at the Lempasing Coastal Fisheries Harbor. The high market demand for yellowstripe scad means fishing for this fish is carried out throughout the year. The aim of this research was to analyze the population dynamics of yellow trevally (Selaroides leptolepis) in the waters of Lampung Bay. The yellow trevally fish collected during the research came from fishermen's catches in the waters around Lampung Bay. The study's findings demonstrated that the yellow trevally's development pattern was negative allometric, and its condition factor value varied between 0.7509 and 1.0842.  the growth parameters of yellowstripe scad obtained an asymptotic length (L∞) value of 152 mm, the growth coefficient (K) of 0.57/year, and theoretical age (t0) of -0.2191 years. Yellow trevally have a natural mortality value (M) of 0.80 per year, a fishing mortality value (F) of 1.12 per year, and a total mortality value (Z) of 1.92/year. Yellowstripe scad recruitment peaked in the Sunda Strait between May and September, at 18.19% and 13.90%, respectively.